Czech Republic : Staff Report for the 2010 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The key findings of the Czech Republic's 2010 Article IV Consultation are discussed. Large foreign direct investment inflows fostered trade integration, underpinning an export-led expansion. Higher initial standard of living contained consumption convergence pressures. An improved fiscal performance contributed to the comfortable external position. This, combined with credible inflation targeting, resulted in generally low inflation and interest rates. A liquid and conservative banking sector limited the build-up of balance sheet vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet